2003
DOI: 10.1071/py03007
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Health and Symptoms in Narcolepsy: A to-year Longitudinal Study

Abstract: This longitudinal study investigated, over a 10-year period, reported changes in people with narcolepsy (a disorder of excessive daytime sleepiness). The issues of the functional impact of symptoms; stimulant medication status; body mass index, and concomitant illnesses were examined. The study also documented, using retrospective report, environmental factors influencing narcolepsy severity, and reported time of worst symptom severity following narcolepsy onset. In 1991, 127 people with diagnosed narcolepsy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Three studies have evaluated the longitudinal evolution of narcolepsy symptoms; however, they were limited by the retrospective nature of the research 10–12. While some reported no changes in daytime sleepiness,10,11 Büchele et al reported that sleepiness is not always stable, with reported spontaneous deterioration or improvement in 27% 12. To the best of our knowledge, no study has specifically and prospectively addressed the course of cataplexy over time.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have evaluated the longitudinal evolution of narcolepsy symptoms; however, they were limited by the retrospective nature of the research 10–12. While some reported no changes in daytime sleepiness,10,11 Büchele et al reported that sleepiness is not always stable, with reported spontaneous deterioration or improvement in 27% 12. To the best of our knowledge, no study has specifically and prospectively addressed the course of cataplexy over time.…”
Section: Introductionmentioning
confidence: 99%
“…9 More recently, impaired cognition, inattention, and a high prevalence of mood disorders have been reported in cross-sectional studies of patients with narcolepsy, suggesting a broad range of comorbidities that affect quality of life and daytime functionality. 10,11 To gain better understanding of the narcolepsy disease experience for future drug development, the United States Food and Drug Administration (FDA) held a public meeting entitled "Narcolepsy Patient-Focused Drug Development" on September 24, 2014 with narcolepsy advocacy groups and patients with narcolepsy.…”
Section: Introductionmentioning
confidence: 99%
“…As a lifelong disease, narcolepsy was reported to destroy the stability of the cortex and induced a decline in attention, reaction, executive ability and cognitive function (19)(20)(21)(22). As a significant number of patients have the disease onset in adolescents, which is considered as the golden period for learning in one's life (23,24), it was important to find the potential influence on school/work performance.…”
Section: Discussionmentioning
confidence: 99%